Genetic Polymorphism and the Rate of Development of Complications in Pneumonia of Varying Genesis - T. V. Smelaya; L. Ye. Salnikova; V. V. Moroz; A. M., Golubev; Yu. V. Zarzhetsky; A. V. Rubanovich (Общая реаниматология, 2011)
Objective: to study the genetic polymorphism of the genes of phase I and II xenobiotic detoxification (GSTM1, GSTP1, GSTT1, CYP1A1), as well as ACE, CCR5, MTHFR, and those of the cytokines IL-6 and TNF-a to reveal hereditary predisposition to pneumonia of varying genesis and its complications. Materials and methods. The frequency of the allele variants of 7 genes was studied in the groups of patients with pneumonia (n=524) and healthy donors (a control group (n=178). Results. There were are genotypes associated with predisposition to community-acquired and nosocomial pneumonia (CAP and NP): GSTM I*, CYP1A1 606T/T, ACE D/D and those associated with a higher risk for complicated CAP. There were effects of the allelic variants of the ACE gene in developing complications, such as acute respiratory distress syndrome, multiple organ dysfunction, and sepsis: ACEI/I insertion homozygotes linked to survival and the alternative ACE D/D genotype to mortality. Conclusion: The study revealed an association of detoxification gene polymorphism with predisposition to CAP and NP and with the development of complications in CAP. Key words: xenobiotic detoxification genes, key ACE renin-angiotensin system gene, chemokine receptor 5 (CCR5) gene, pneumonia, acute respiratory distress syndrome, sepsis, multiple organ dysfunction.